The statutory prohibition of market manipulation in Zimbabwe - Princess Thembelihle Ncube; Howard Chitimira (Juridical Tribune, 2020)
Market manipulation includes, inter alia, a practice that interferes or attempts to interfere with the free and fair operation of the securities and financial markets by creating an artificial, false or misleading appearance of the price of, or market for, the relevant securities, commodities or financial instruments. Consequently, market manipulation is treated as an offence in many countries, including Zimbabwe. For instance, market manipulation is expressly prohibited under the Securities Act 17 of 2004 (Chapter 24: 25) as amended (Securities Act 2004). In light of this and for the purposes of this article, the adequacy of the statutory prohibition on market manipulation in Zimbabwe will be examined. Accordingly, selected key elements, types, examples, penalties and definitional aspects of the market manipulation offence under the Securities Act 2004 are discussed. This is done to unpack and examine the adequacy of the Securities Act 2004 in relation to the combating of market manipulation in the Zimbabwean financial markets. It is hoped that the recommendations enumerated in this article will enable policy makers to develop optimal regulatory measures that promote investor protection and effectively combat market manipulation in the Zimbabwean financial markets.